Pelaksanaan Korps Musik (Korsik) Upacara Bendera Di SMA Tamansiswa Padang - Bayu Dimas Saputra; Esy Maestro (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The purpose of this study was to describe the implementation of the Music Corps (Korsik) at the Flag Ceremony at Tamansiswa Padang High School. The type of research used is qualitative research with descriptive analysis methods. The types of data used to examine the object are primary data and secondary data. The techniques used in data collection are literature study, observation, interviews, and documentation. Data analysis techniques by identifying, clarifying, and concluding data. The results of the study showed that there were still obstacles and obstacles during the corps music practice and there were still students who were not present when the ceremony started, besides that the corps musical instruments at school were inadequate so that the training process and during the corps implementation were slightly hampered. The implementation of the flag ceremony music corps at Tamansiswa Padang High School was carried out through several stages during the training, namely the trainer prepared the material to be taught to students. The main purpose of holding a music corps at Tamansiswa High School is to accompany the music during the flag ceremony on the Tamansiswa campus. Tamansiswa Padang High School is entrusted with accompanying the music for the flag ceremony. The Principal of SMA Tamansiswa Padang provided music facilities for SMA Tamansiswa Padang students and an arts and culture teacher as well as a coach, immediately made a music corps training schedule with the aim of carrying out the performance of the Flag Ceremony Music Corps.